Answer: c
Step-by-step explanation:
Yea
Answer:
y = -18
General Formulas and Concepts:
<u>Pre-Algebra</u>
- Order of Operations: BPEMDAS
- Equality Properties
<u>Algebra I</u>
- Solving systems of equations using substitution/elimination
Step-by-step explanation:
<u>Step 1: Define systems</u>
y = 5x - 3
3x - 2y = 27
<u>Step 2: Rewrite systems</u>
- Define: 3x - 2y = 27
- Add 2y on both sides: 3x = 2y + 27
- Divide 3 on both sides: x = 2/3y + 9
<u>Step 3: Redefine</u>
y = 5x - 3
x = 2/3y + 9
<u>Step 4: Solve for </u><em><u>y</u></em>
- Substitute in <em>x</em>: y = 5(2/3y + 9) - 3
- Distribute 5: y = 10/3y + 45 - 3
- Combine like terms: y = 10/3y + 42
- Subtract 10/3y on both sides: -7/3y = 42
- Divide -7/3 on both sides: y = -18
Answer:
5
Step-by-step explanation:
5
Answer:
x=(3a+5)/(2a-b)
Step-by-step explanation:
We spread the a to the 2x and -3 first,
2ax -3a= bx+5 5ax
By adding 3a, we pass the -3a over
2ax=bx+5+3aa bx+5+3aa
We'll pass the bx over the bx, then
2ax-bx=5+3aa-bx=5
Now we will party like this on the left side,
5+3a) x(2a-b)=5+3a)
Everything we have to do to find x is to separate both sides by (2a-b)
x=(3a+5)/=(3a+5)/ (2a-b)
Answer:
B. $ 1.30
Step-by-step explanation: